Scalar Implicature, Hurford's Constraint, Contrastiveness and How They All Come Together - Tomioka, Satoshi (Frontiers in Communication, 2021)
Disjunction with two scalar items, such as some or all of the books, has been re- garded as evidence for the grammatical theory of scalar implicature (e.g., Chierchia, Fox and Spector 2012). Hurford's Constraint (Hurford 1974) provides that disjuncts are banned from having an entailing relation, and to make such a disjunction comply Hurford's Constraint, the meaning of some must be locally strengthened. Interestingly, however, the order of dis- joined scalar items is not free, as noted by Singh (2008). The order in which a weaker scalar item comes rst followed by its stronger scalar mate is better than the other order. I present an analysis of this ordering restriction based on the novel observation that the restriction is not only found in disjunction but in contrastive environments in general. I propose that contrasting a linguistic expression requires a 'contrast antecedent', which must elicit a set of mutually exclusive alternatives that includes the meaning of the contrasted expression. It will be demonstrated how the mutual exclusivity requirement presents a principled explana- tion for the ordering asymmetry. One of the indispensable ingredients in the proposal is the grammatical/conventional generation of scalar implicatures, as the strengthened meaning must be the basis of alternatives. The paper also provides a speculative analysis of only, in which I suggest that the process of exhausti cation in the grammatical theory of scalar implicature should not be characterized as the implicit only, as their semantic contributions are more different than commonly assumed